A digital twin-based flexible cellular manufacturing for optimization of air conditioner line. (January 2021) - Guo, Hongfei; Chen, Minshi; Mohamed, Khalgui; Qu, Ting; Wang, Siming; Li, Jianke
Highlights: It is determined that a certain air conditioning production line needs to optimize the complex coupling problems such as layout, process capability, logistics, test equipment and so on. Based on the coupling problem, we construct a novel optimization model, which combines Digital Twin and flexible cellular manufacturing. An event mechanism-based decoupling method is put forward and it combines with multi-objective optimization to solve coupling problems. A general procedure and framework for optimization is proposed for each coupling problem. A case study of an air conditioner production line verifies the superiority of the proposed improved model over traditional production methods. With the construction of the improvement model based on digital twins, simulation analysis and practical application, the production layout, process balance, accurate logistics and intelligent equipment of the production line have been greatly improved. Finally, a closed-loop model for long-term production line improvement is designed. The method of this paper can be applied to the intelligent manufacturing field of household appliances, especially for the development of the theory of the modeling and simulation of DT, as well as the practice of industrial application of DT. Abstract: In a personalized and various production mode, the production line needs to be updated quickly to meet market demand. The Optimization of production line is taken as the object. To address the coupling problems, such as unreasonable production line layout, unbalanced process capability, inaccurate logistics distribution and unintelligent equipment testing, a method of flexible cellular manufacturing based on digital twin is put forward. Decoupling based on event mechanisms and multi-objective optimization will be used in the design of methods, which will be continuously optimized in the simulation and will eventually be validated. After the implementation of an air conditioner line, the production capacity increased by 58.3 %, the WIP decreased by 77.8 %, the balance rate of the production line increased by 25.2 %, and the per capita production capacity increased by 29.8 %. The number of operators decreased by 28.3 %. The results show that the optimization method of flexible cellular manufacturing based on digital twin has practical value and guiding significance to improve the efficiency of production line.